A study on the length of stay of neonates in neonatal intensive care unit in a referral hospital in India - P., Kanimozhi; K. S., Kumaravel; K., Velmurugan (International Journal of Contemporary Pediatrics, 2019)
Background: Estimate of length of stay is important while counseling the parents of preterm infants and also make them prepared psychologically. Methods: A retrospective study done in the Neonatal Intensive Care Unit (NICU) of Government Mohan Kumaramangalam medical college hospital, Salem, Tamil Nadu, India between December 2017 and November 2018. All the neonates admitted during the study period formed the study group. Results: There were 3902 neonates admitted in the NICU during the study period. The mean duration of stay of neonates in the NICU during the study period was 7 days. Out of 3902 neonates in the study group, 37 (0.94%) neonates stayed less than 24 hours, 2208 (56.58%) neonates stayed for 1 to 5 days, 929 (23.8%) neonates stayed for 6 to 10 days, 668 (17.11%) neonates stayed between 11 to 30 days, 41(1.05%) neonates stayed for 31 to 60 days and 7 (0.18%) neonates stayed for more than 61 days. About 45% of neonates in the birth weight category of 1001 to 1500g stayed for 11 to 30 days. A similar trend was also observed in the analysis of length of stay of 29 to 32 weeks preterm neonates. Conclusions: Every hospital should have their own data to predict the length of stay of neonates in NICU. Future directions should include strategies in reducing the length of stay in NICU thereby optimising resources for the parents and the country.